Application of Laser Shock Processing - Brajer, Jan; Mádl, Jan; Švábek, Roman; Pitrmuc, Zdeněk; Rostohar, Danijela; Zeman, Pavel; Ocaña, José Luis (Manufacturing Technology Journal, 2015)
Laser Shock Processing (LSP), or strengthening the material surface by laser shock wave is very modern and progressive technique, which allows a significant increase in fatigue life of cyclically loaded parts. The compressive residual stresses are generated in the surface layer of material processed by laser beam, which can significantly improve the fatigue properties of the material and reduce the initiation and propagation of the surface cracks. This technique finds practical use of the most demanding applications like in the aerospace industry. For this reason, we are mapping the selected surface properties after the laser treatment for the better understaning of technology possibilities. After that another suitable applications can be found. It is also important to determine appropriate parameters for different types of material and requirements affecting the result.
Keywords: Laser shock processing; surface integrity; residual stress